2010
DOI: 10.1103/physrevd.82.011101
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the decayX(3872)J/ψω

Abstract: We present a study of the decays B 0,+ → J/ψπ + π − π 0 K 0,+ , using 467×10 6 B B pairs recorded with the BABAR detector. We present evidence for the decay mode X(3872) → J/ψω, with product branching fractions B(B + → X(3872A detailed study of the π + π − π 0 mass distribution from X(3872) decay favors a negative-parity assignment.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 165 publications
(60 citation statements)
references
References 32 publications
7
53
0
Order By: Relevance
“…Moreover, the isospin breaking effect is amplified by the tiny binding energy. As an example, when the binding energy is 0.3 MeV, they found that the isovector component inside the X(3872) is 26%, and the ratio of the two hidden-charm decay modes B(X(3872) → π + π − π 0 J/ψ)/B(X(3872) → π + π − J/ψ) was estimated to be 0.42, consistent with the experimental value [75,90].…”
Section: Molecular Schemesupporting
confidence: 71%
See 4 more Smart Citations
“…Moreover, the isospin breaking effect is amplified by the tiny binding energy. As an example, when the binding energy is 0.3 MeV, they found that the isovector component inside the X(3872) is 26%, and the ratio of the two hidden-charm decay modes B(X(3872) → π + π − π 0 J/ψ)/B(X(3872) → π + π − J/ψ) was estimated to be 0.42, consistent with the experimental value [75,90].…”
Section: Molecular Schemesupporting
confidence: 71%
“…which were observed by Belle [75] and BaBar [90], respectively. The difference between B 0 → K 0 X and B ± → K ± X also attracted much experimental interest.…”
Section: The Charmonium-like Xyz Statessupporting
confidence: 62%
See 3 more Smart Citations